Analysis of the Influence of Strategic Trends: Methodological Aspect and Application at the Regional Level - R. I. Gerelishin (Управленческое консультирование)
The article is devoted to the consideration of issues of analysis of strategic trends of various levels and nature in the context of the impact on the socio-economic development of regions. The purpose of the study is to expand the tools for trend analysis, as one of the key stages in developing the concept of a strategy for the socio-economic development of regions in accordance with the strategizing methodology of a foreign member of the Russian Academy of Sciences, Doctor of Economic Sciences, Professor V. L. Kvint. At the same time, the presented tools are relevant both to regional strategizing in general and can be used in the development of industry and corporate strategies. A hierarchical structure of trends, a scheme for decomposing trends into channels of influence, and proposals for the procedure for assessing their individual and joint influence are presented, for which both econometric modeling and statistical methods, as well as expert assessments, can be used. The application of the presented proposals is demonstrated by the example of decomposition and analysis of global trends, however, a similar algorithm is applicable for national, regional and subregional trends. Based on the results of the analysis, the conclusions were confirmed that trends contain and create multidirectional impulses for the strategized object, capable of both enhancing and neutralizing each other, and therefore they need to be analyzed in detail and taken into account when developing regional strategies to achieve maximum efficiency.